PERBANDINGAN POLA ROMBAK SELULOSA OLEH BEBERAPA JAMUR BASIDIOMYCETES - RAHMANSYAH, MAMAN (BERITA BIOLOGI, 1989)
MAMAN RAHMANSYAH, 1989,Comparative capability of cellulose degradation by Basidiomy cetes fungi.Berita Biologi 3(9) 450 - 453.Cellulosa is natural resource that still found abandon and its can be composted by themselves naturaly to the earth.Basidiomycetes fungi offered to convert those waste organic matter into useful product.Four Basidiomycetes fungi (Auricularia polytricha, Coprinus cinereus, Pleurotus qstreatus and Volvariella valcacea) have been tested to degrade riee straw, Whatman filter paper and cellulose powder. Three replicates of 3 grams of media were inoculated by different fungus land were fermented for 21 days at room temperature (± 28 C). Biodegradation rare was measured by the lost weight basis of media and bioconvertion rate was detected by stating ability of enzime (cellulose), which were extracted from cellulose powder culture,to convert CMC substrat and glucose production.The result shows that C. cinereus has almost 3 to 4 times degrading and converting capability compared to other fungi.